NEW ASTRONOMICAL STATION ON MOUNT DUSHAK-EREKDAG. 1. THE STATION. - Dorokhov, N. I.; Dorokhova, T. N.; Komarov, N. S.; Mukhamednazarov, S. (Одеські астрономічні публікації, 2017)
A new observational station of astronomical observatory of Odessa State University was put into operations in Kopet-Dag Mountains in Turkmenistan in summer 1992. The site has coordinates φ= +37°56’ N, λ = 3h52m E; an altitude 2020 m. A meteorological characteristics and data on sky transparency are given. First observations of different objects show a good quality of data.